An injectable elastic hydrogel crosslinked with curcumin–gelatin nanoparticles as a multifunctional dressing for the rapid repair of bacterially infected wounds. (20th March 2023) - Cai, Xiaohui; He, Yutong; Cai, Liu; Zhan, Jiamian; Li, Qian; Zhong, Saiqiong; Hou, Honghao; Wang, Wenya; Qiu, Xiaozhong
Abstract : An injectable elastic hydrogel as a multifunctional dressing is reported for the rapid repair of bacterially infected wounds. Abstract : Injectable self-healing hydrogel dressings with excellent elasticity and multifunctional repair effects have been in high demand in wound healing applications, while maintaining stable elasticity in injectable multifunctional hydrogel dressings is still a challenge. Based on carboxymethyl chitosan (CMCS), curcumin–gelatin nanoparticles (CG NPs), and sodium alginate oxide (OSA), we developed a double-crosslinking injectable elastic self-healing hydrogel without any chemical cross-linking agent as a multifunctional wound healing dressing. CG NPs were more stable than pure curcumin (Cur) nanoparticles and could regulate the cross-linking of injectable hydrogels for high elasticity and rapid self-healing. We found that the CG NPs endowed the injectable hydrogel with good anti-inflammatory, antibacterial, and reactive oxygen scavenging activities and could significantly shorten the wound healing time in infected full-thickness skin defect rats by promoting the polarization of M2-type macrophages, reducing oxidative damage, accelerating collagen deposition, enhancing granulation formation, and elevating angiogenesis. Taken together, the tunable elastic injectable hydrogel dressing exhibited a long-term service life with sustained repair function and can be taken as an optimal candidate for bacteria-infected wound healing.